Analisis Statistik Kecemasan dan Kemampuan Dasar pada Ekstrakurikuler Basket Putra di SMA Negeri 1 Sukoharjo - Winata, Garin AJi; Dwijayanti, Karlina; Nugroho, Untung (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The purpose of this study is to examine and identify the levels of anxiety and basic basketball skills among male students participating in the basketball extracurricular at SMA Negeri 1 Sukoharjo. This research is expected that accurate data can be obtained regarding the relationship between anxiety levels and the mastery of fundamental basketball techniques among students. This study employs a descriptive statistical approach. The sampling technique used is total sampling, with data collected through an anxiety level test and a basic basketball skill assessment. Based on the results of the anxiety and basic skill assessments, the majority of participants were in the "moderate" category, with a percentage of 38.78% or 19 students. The lowest category for anxiety was "very low," with 8.16% or 4 students. Regarding basic skill levels, most participants fell into the "average" category, with 34.69% or 17 students. The lowest categories, "very poor" and "poor," each accounted for 0% or no participants. These findings indicate that out of 49 participants, only six students exhibited very high anxiety levels, while only three students demonstrated basic basketball skills categorized as excellent.